Competition and the Residential Land Allocation Process - Mills, David E. (Quarterly Journal of Economics, 1978)
I. Introduction, 227.—II. The residential land allocation process, 228.—III. The socially efficient RLAP, 230.—IV. The competitive RLAP, 231.—V. Distortion and the property tax, 234.—VI. Conclusion, 240.—Appendix: statement of the necessary conditions for socially efficient RLAP's and proof of the equivalence theorem, 240.